2018
DOI: 10.3892/etm.2018.6474
|View full text |Cite
|
Sign up to set email alerts
|

Research on the changes in balance motion behavior and learning, as well as memory abilities of rats with multiple cerebral concussion-induced chronic traumatic encephalopathy and the underlying mechanism

Abstract: To study the effects of multiple cerebral concussion (MCC)-induced chronic traumatic encephalopathy on balance motion behavior learning and memory abilities of rats and its possible mechanism. 4MCC rat models were established by means of striking the head (4MCC group, n=15), while normal Sprague-Dawley (SD) rats were used as controls (C group, n=15). At 2 weeks after injury, balance beam (BB) test, beam walking (BW) test and Morris water maze (MWM) test were performed, respectively. The metabolites in brain ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It is important to note the differences in subjects, injury model, and number of injuries and intervals between these studies. Those studies examining a single acute (< 30 days) timepoint also showed variability; a weight drop injury showed no tau histology changes in brainstem at 1d ( 116 ), a frontal pendulum rmTBI showed decreased pTau at 14 days ( 117 ), and a weight drop in mice showed increased p-tau at 30 days ( 118 ). The remaining studies examining a single chronic time point showed some increase in p-tau but they were not robust ( 119–121 ), and one study showed p-tau even decreased compared to 1 day ( 122 ).…”
Section: Pathological Tau Changes: Evidence Of Tau After Mild and Rep...mentioning
confidence: 99%
“…It is important to note the differences in subjects, injury model, and number of injuries and intervals between these studies. Those studies examining a single acute (< 30 days) timepoint also showed variability; a weight drop injury showed no tau histology changes in brainstem at 1d ( 116 ), a frontal pendulum rmTBI showed decreased pTau at 14 days ( 117 ), and a weight drop in mice showed increased p-tau at 30 days ( 118 ). The remaining studies examining a single chronic time point showed some increase in p-tau but they were not robust ( 119–121 ), and one study showed p-tau even decreased compared to 1 day ( 122 ).…”
Section: Pathological Tau Changes: Evidence Of Tau After Mild and Rep...mentioning
confidence: 99%